Complexes of HXeY with HX (Y, X = F, Cl, Br, I): Symmetry-Adapted Perturbation Theory Study and Anharmonic Vibrational Analysis - Bartosz Dzięcioł; Irina Osadchuk; Janusz Cukras; Jan Lundell (Molecules, 2023)
A comprehensive analysis of the intermolecular interaction energy and anharmonic vibrations of 41 structures of the HXeY⋯HX (X, Y = F, Cl, Br, I) family of noble-gas-compound complexes for all possible combinations of Y and X was conducted. New structures were identified, and their interaction energies were studied by means of symmetry-adapted perturbation theory, up to second-order corrections: this provided insight into the physical nature of the interaction in the complexes. The energy components were discussed, in connection to anharmonic frequency analysis. The results show that the induction and dispersion corrections were the main driving forces of the interaction, and that their relative contributions correlated with the complexation effects seen in the vibrational stretching modes of Xe–H and H–X. Reasonably clear patterns of interaction were found for different structures. Our findings corroborate previous findings with better methods, and provide new data. These results suggest that the entire group of the studied complexes can be labelled as “naturally blueshifting”, except for the complexes with HI.